Quantification of Acipimox in Plasma and Tissues by LC–MS/MS: Application to Pharmacokinetic Comparison between Normoxia and Hypoxia - Xin Shen; Gaofu Li; Libin Wang; Huijin Yu; Lei Zhou; Huifang Deng; Ningning Wang; Chengcai Lai; Wei Zhou; Yue Gao (Molecules, 2022)
This study aimed to evaluate the pharmacokinetics of acipimox in rats under simulated high altitude hypoxia conditions. A sensitive and reliable LC–MS/MS method has been established for the quantitation of acipimox in rat plasma and tissue homogenate and validated according to the guidelines of the European Medicines Agency (EMA) and the US Food and Drug Administration (FDA). Western blotting and enzyme linked immunosorbent assay (ELISA) were used to investigate the expression of lipid metabolism-related proteins and free fatty acid (FFA) levels, respectively. Cell viability was detected using a Cell Counting kit-8 assay (CCK-8). The method was then successfully applied in a pharmacokinetic comparison between normoxic and hypoxic rats. The results indicated that there were significant differences in the main pharmacokinetics parameters of acipimox between normoxic and hypoxic rats. HCAR2 expression in the hypoxia group was upregulated compared to that in the normoxia group and the levels of FFA decreased more in the hypoxia group. Under the hypoxia condition, the proliferation of HK2 cells was inhibited with increasing concentrations of acipimox. The results provide important and valuable information for the safety and efficacy of acipimox, which indicated that the dosage of acipimox might be adjusted appropriately during clinical medication in hypoxia.